Biodegradable microspherical implants containing teicoplanin for the treatment of methicillin-resistant Staphylococcus aureus osteomyelitis - DURMUŞOĞLU, LÜTFİYE (SPRINGER, 2010)
The aim of this study was to prepare poly(d,l-lactide-co-glycolide) (PLGA) microspherical implants containing teicoplanin (TCP) using a double emulsion solvent evaporation method and to evaluate its efficacy for the local treatment of chronic osteomyelitis. The particle size and distribution, morphological characteristics, thermal behaviour, drug content, encapsulation efficiency and in vitro release assessments of the formulations were carried out. Sterile TCP-PLGA microspheres were implanted in the proximal tibia of rats with methicillin resistant Staphylococcus aureus (MRSA) osteomyelitis. After 3 weeks of treatment, bone samples were analysed with a microbiological assay and evaluated histopathologically. Microspheres between the size ranges of 2.01 and 3.91 mu m were obtained. Production yield of all formulations was found to be higher than 82% and encapsulation efficiencies of 33.6-69.8% were obtained. DSC thermogram showed that the TCP was in an amorphous state in microspheres. In vitro drug release studies had indicated that the drug release rate of microspheres was decreased upon increasing the polymer:drug ratio. Based on the in vivo data, rats treated with implants and intramuscular injection showed 1.7 x 10(3) +/- A 1.3 x 10(3) and 5.8 x 10(4) +/- A 5.3 x 10(4) colony forming unit of MRSA in 1 g bone samples (CFU/g), respectively (P < 0.01). The in vitro and in vivo studies had shown that the TCP-PLGA microspheres were effective for the treatment of chronic osteomyelitis in an animal experimental model. Hence, these microspheres may be potentially useful in the clinical setting with the need for further investigation for optimal dosing of TCP-PLGA microspheres.
Keywords: TCP-PLGA implants; Osteomyelitis; MRSA; PHARMACOKINETIC PROPERTIES; DELIVERY-SYSTEM; BONE-INFECTIONS; VIVO EVALUATION; IN-VITRO; CIPROFLOXACIN; THERAPY; RELEASE; MODEL; BEADS